Human rights in the United States : beyond exceptionalism - Hertel, Shareen; Libal, Kathryn , 1968- (Cambridge University Press, 2011)
"This book brings to light emerging evidence of a shift toward a fuller engagement with international human rights norms and their application to domestic policy dilemmas in the United States. The volume offers a rich history, spanning close to three centuries, of the marginalization of human rights discourse in the United States. Contributors analyze particular cases of U.S. human rights advocacy aimed at addressing persistent inequalities within the United States itself, including advocacy on the rights of persons with disabilities; indigenous peoples; lone mother-headed families; incarcerated persons; lesbian, gay, bisexual, and transgendered people; and those displaced by natural disasters, most notably Hurricane Katrina. The book also explores key arenas in which legal scholars, policy practitioners, and grassroots activists are challenging multiple divides between "public" and "private" spheres (for example, in connection with children's rights and domestic violence) and between "public" and "private" sectors (specifically, in relation to healthcare and business and human rights)"